1991
DOI: 10.1128/jb.173.3.1073-1079.1991
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. phaseolicola genomic clones harboring heterologous DNA sequences suppress the same phaseolotoxin-deficient mutants

Abstract: Cosmid cloning and mutagenesis were used to identify genes involved in the production of phaseolotoxin, the chlorosis-inducing phytotoxin of Pseudomonas syringae pv. phaseolicola, the causal agent of halo blight of bean (Phaseolus vulgaris L.). Eight stable clones were isolated from a genomic cosmid library by en masse mating to 10 ethyl methanesulfonate (EMS)-induced Tox-mutants. In cross-matings, each suppressed all 10 mutants as well as an additional 70 EMS-induced Tox-mutants (and one UV-induced Tox-mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Three TnS mutants, TNM5, TNM7, and TNM11, previously obtained by random Tn5 mutagenesis of the chromosome of the wild-type strain (13), were complemented by pHK120, implying that the Tn5 insertions were located within the chromosomal region represented by the insert in pHK120. Southern blots of the genomic DNA from the three TnS mutants were probed with 32P-labeled pHK120 DNA, and a comparison of the size of the hybridizing genomic fragments from the three mutants with that of pHK120 revealed that the insertions were located within the pHK120 region at the positions denoted by the symbol # (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three TnS mutants, TNM5, TNM7, and TNM11, previously obtained by random Tn5 mutagenesis of the chromosome of the wild-type strain (13), were complemented by pHK120, implying that the Tn5 insertions were located within the chromosomal region represented by the insert in pHK120. Southern blots of the genomic DNA from the three TnS mutants were probed with 32P-labeled pHK120 DNA, and a comparison of the size of the hybridizing genomic fragments from the three mutants with that of pHK120 revealed that the insertions were located within the pHK120 region at the positions denoted by the symbol # (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike pDC938, pHK120 (a class I clone) complements five chromosomal Tn5 mutants in addition to the UV-and ethyl methanesulfonate-induced mutants (13). The complementation of all five TnS mutants by pHK120 suggested that its insert harbored a cluster of genes involved in phaseolotoxin production, because the Tn5 insertions in the mutants are located in different chromosomal EcoRI fragments.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…phaseolicola (Psp). The genes involved in the production of these toxins have been cloned and characterized (Xu and Gross 1988;Willis et al 1991;Kamdar et al 1991). These genes may be located in one or more clusters.…”
Section: Symptom Expressionmentioning
confidence: 99%